Emergency medicine residents’ interpretation of computed tomography scans in patients presenting with suspected acute appendicitis improve after training - Degerli, Vermi; Mollamehmetoglu, Hulya (Annals of Medical Research, 2021)
Aim: Abdominal computed tomography (CT) is considered as the best imaging tool in the diagnosis of acute appendicitis (AA) in adults. Since most medical centers do not have access to immediate radiological assessment, emergency physicians (EPs) may have to interpret CTs when they need to make immediate clinical decisions. Therefore, it has become a necessity for EPs to achieve a certain level of imaging experience. The aim of our study was to evaluate the effect of a short educational intervention on the ability of emergency medicine residents (EMRs) to interpret AA criteria and diagnose AA using abdominal CT.Material and Methods: Our study was an intervention study evaluating the effectiveness of education. The EMRs were given a 2-hour didactic session on “abdominal CT interpretation in the diagnosis of AA” by an experienced radiologist. Abdominal CTs of 39 patients with a final diagnosis of AA and 8 patients with other diagnoses were interpreted by four senior EMRs (3rd- and 4th-year residents) and three junior EMRs (1st- and 2nd-year residents) before and 2 weeks after the didactic session. Interpretations by the EMRs were compared with the radiologist’s interpretations and classified as agreement or disagreement.Results: Interpretation skills of senior EMRs before and after educational intervention showed considerable improvement in the rate of agreement (before vs after % agreement) didactic teaching as follows: enlargement of the appendix (72.3% vs. 86.2%), appendiceal wall thickening (69.7% vs. 81.9%), heterogeneous wall enhancement (46.8% vs. 61.2%), periappendiceal inflammation (63.8% vs. 79.8%), and AA diagnosis (73.4% vs. 88.8%), but not for appendicolith (79.8% vs. 77.7%). Junior EMRs showed no changes following the intervention. Conclusion: After a short educational intervention, the senior EMRs showed significant improvement in interpreting AA diagnoses and abdominal CT criteria compared to junior EMRs.
Keywords: Appendicitis; computer-assisted; education; image interpretation